IMPACT OF COW MANURE APPLICATION AS SOIL AMENDMENT ON ESSENTIAL OIL COMPOSITION AND METAL CONTENTS IN FENNEL (Foeniculum vulgare Mill) (Applied Biological Research, 2023)
The natural resources and agriculture ecosystem are adversely damaged  due to the fast buildup of toxic pollutants such as radionuclide, organic  contaminants and heavy metals emitted from industries and other  anthropogenic activities. A polyhouse experiment was conducted to assess  the capability of fennel (Foeniculum vulgare) to remediate a metal  contaminated soil, collected from Moradabad (a hub of electroplating  industries), by the application of different levels of cow manure. Metal  analysis of root and aerial parts was performed using AAS and essential oil composition by GC and GC/MS. The results revealed that the use of  cow manure at 52 t ha-1 gave highest plant growth and oil yield. Limonene,  trans-anethole and dillapiole were the major constituents among all the  amendments. The highest content of trans-anethole (56.05%) was noticed  at 52 t ha-1. The addition of cow manure reduced Zn, Ni, Cu and Cr  concentration in plant tissues. Maximum reduction was found at 104 t ha-1.  Cr showed highest BCF at 0 t ha-1, while Cu showed lowest BCF at 104 t  ha-1. Therefore, cow manure use in the metal contaminated soils had  favourable impact on the growth characters and essential oil composition  of fennel.
Keywords: Cow manure; essential oil; Foeniculum vulgare; heavy metals